Perlindungan Institusi Perkawinan Melalui Asas Mempersulit Perceraian: Tinjauan Maqashid Al-Syariah Terhadap Peraktik Di Pengadilan Agama Sinjai: An Analysis of Maqasid al-Syari‘ah on Practices in the Sinjai Religious Court - Ariani, Akmal; Yusuf, Muh.; Has, Nisaul Haq Bintu (Universitas Islam Negeri Alauddin Makassar, 2025)
This study is motivated by the high divorce rate in Indonesia, which has implications for the fragility of the family institution and the weakening of social resilience, thus requiring legal mechanisms that can provide protection for the institution of marriage. One of the mechanisms applied in the religious court system is the principle of making divorce difficult, which normatively serves to prevent non-urgent divorces. This study aims to analyze the implementation of this principle in the Sinjai Religious Court and review its relevance to maqāṣid al-syarī‘ah. The research method uses a qualitative approach with a juridical-empirical model. Data were collected through court observations, interviews with judges, mediators, and litigants, as well as document and literature studies. The research instruments consisted of interview guidelines and field notes, while data analysis was carried out through the stages of reduction, data presentation, and conclusion verification. The results of the study show that the principle of making divorce difficult is implemented from the early stages of case registration, with the panel of judges attempting to reconcile the parties through advice and mediation in accordance with Supreme Court Regulation Number 1 of 2016. These reconciliation efforts continue throughout the trial process through a persuasive approach and the appointment of an official mediator. However, the application of this principle faces a number of obstacles, such as long-standing domestic conflicts, local cultural factors that tend to be permissive towards divorce, and economic pressures on families. From the perspective of maqāṣid al-syarī‘ah, the principle of making divorce difficult is in line with the objectives of protecting religion, life, reason, offspring, and property, while reducing the social harm caused by unnecessary divorce. Thus, the application of this principle in the Sinjai Religious Court serves not only as a formal procedure but also as a substantive instrument in maintaining the continuity of marriage, preventing premature divorce, and providing space for domestic reconciliation through mediation.